Assessing the consistency of liver fibrosis results obtained through biopsy and transient elastography in patients suffering from chronic hepatitis C - Pokora, Agnieszka; Kiciak, Sławomir; Tomasiewicz, Krzysztof (Clinical and Experimental Hepatology, 2016)
Until recently, core-needle liver biopsy was used as the gold standard in chronic hepatitis C diagnostics. Information on the inflammatory activity grade and the staging of liver fibrosis or steatosis, obtained through biopsy, constituted an indispensable element in the process of determining patients’ eligibility for antiviral treatment. The histological profile of the samples examined was decisive in determining the time for commencing treatment. Given that this procedure involves the risk of complications and temporarily reduces patient living comfort, it was deemed necessary to search for other ways to assess liver fibrosis. Transient elastography is a non-invasive alternative to liver biopsy. The current chronic hepatitis C treatment programme provides the possibility to perform transient elastography instead of liver biopsy. The test result is expressed in kPa. However, liver biopsy is still recommended in certain cases of unclear aetiology, or if discrepancies are found between the elastography results and patient clinical condition. The aim of this study was to compare two methods of liver fibrosis assessment in terms of consistency of results, and to analyse any inconsistent results.